Captain Cook chased a chook : children's folklore in Australia - Factor, June, 1936- (Ringwood, Vic. : Penguin, 1988)
Includes chapter on Aboriginal childrens play.
Includes index.
Includes index.
Bibliography: p. 265-281.
White, K. Bibliography of Australian children's books
Keywords: Children -- Australia -- Folklore; Folklore and children -- Australia; Settlement and contacts - Explorers; Australia